MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Dina Islamiyah (Departemen Matematika, 2020)
Learning mathematics has several goals that must be achieved, one of which is thenability tonsolve mathematical problems. Themobservation results indicate thatmthe students mathematical problem solving abilities at SMPN 12 Padang were still low. Therefore, efforts are needed to overcome this in the form ofnthe Creative Problem Solving (CPS) learning model that canmimprovemstudents mathematicalmproblem solving abilities. Thempurpose ofmthis research was tomdescribe how the Creative Problem Solving (CPS) learning model can improvenstudents mathematical problem solving abilities and describe themform ofnlearning tools in the application ofnthe Creative Problem Solving (CPS) learning model. Thentype ofmresearch wasliterature study onnthe Creative Problem Solving (CPS) learning model. Themconclusion ofnthe researchmwas theoreticallymthe Creative Problem Solving (CPS) learning model could improvemstudents mathematical problem solving abilities. Keywords—Creative Problem Solving (CPS) Learning Model, mathematical problem solving abilities